Influential Factors and Efficacy Analysis of Tacrolimus Concentration After Allogeneic Hematopoietic Stem Cell Transplantation in Children with β-Thalassemia Major - Li C; Lu J; Zhou S; Wei Y; Lv C; Liu T; Wu Y; Wu D; Qi J; Cai R (Dove Medical Press, 2021)
Chengxin Li,* Jiejiu Lu,* Siru Zhou, Yinyi Wei, Chunle Lv, Taotao Liu, Yun Wu, Dongni Wu, Jianying Qi, Rongda Cai Department of Pharmacy, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Taotao LiuDepartment of Pharmacy, The First Affiliated Hospital of Guangxi Medical University, No. 6 Shuangyong Road, Nanning, 530021, Guangxi Province, People's Republic of ChinaTel +86 7715356789Email liutaotao@gxmu.edu.cnPurpose: To analyze factors influencing tacrolimus (TAC) trough concentration (C0) in β-thalassemia major (β-TM) pediatric patients after allogeneic hematopoietic stem cell transplantation (Allo-HSCT) and to investigate the effects of genotype polymorphism and drug-drug interactions on TAC trough concentration in children with β-TM. Furthermore, to analyze the correlation between TAC C0 and efficacy and adverse reactions.Patients and Methods: Prospectively collection of demographic information and details of combined treatment of patients with β-TM receiving HSCT, and genotypes of CYP3A4, CYP3A5, and ABCB1 (rs1045642, rs1128503, rs2032582) were obtained for each patient. Univariate analysis and multiple linear regression analysis were used to investigate influencing factors on TAC C0. The impact of different genotypes and the co-administration of azole antifungal drugs on β-TM patients receiving TAC were evaluated, together with the correlation between acute graft-versus-host disease (aGVHD), infection, and liver injury of TAC C0.Results: A total of 46 patients with 587 concentration data were included. The multiple linear regression results showed that the patient's sex, weight, postoperative time, hemoglobin, platelet count, serum cystatin C, and combined voriconazole were independent influencing factors of the infusion trough concentration/daily dose, C0/Div. Age, body surface area, postoperative time, co-administration of voriconazole, and CYP3A4*18B are independent influencing factors of C0/Dpo. Group comparisons showed that voriconazole can affect TAC C0 administered intravenously (IV) and orally in β-TM pediatric patients, while patient genotype can affect TAC C0 during oral administration. TAC C0 does not correlate with aGVHD or liver injury, but infection may be associated with TAC C0.Conclusion: The concentration of TAC should be closely monitored when co-administered with voriconazole. It is worth considering that the influence of genotype on the trough concentration of oral TAC and individualized drug administration warrant investigation. Finally, this study indicated that C0 is not suitable as an indicator of the efficacy of TAC.Keywords: β-thalassemia major, allogeneic hematopoietic stem cell transplantation, tacrolimus, trough concentration